1993
DOI: 10.1172/jci116613
|View full text |Cite
|
Sign up to set email alerts
|

Ulcerative colitis: a genetically heterogeneous disorder defined by genetic (HLA class II) and subclinical (antineutrophil cytoplasmic antibodies) markers.

Abstract: Newly described distinct associations of HLA class II genes with ulcerative colitis (UC) (DR2) and Crohn's disease (CD) (DR1 /DQ5) provide strong evidence for genetic heterogeneity of susceptibility between these two forms of inflammatory bowel disease. A familial distribution of antineutrophil cytoplasmic antibodies (ANCAs, a subclinical marker of UC) in UC families has further implied the existence of heterogeneity within UC.To test the hypothesis that the heterogeneity within UC indicated by ANCAs has a gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
50
2
1

Year Published

1995
1995
2014
2014

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 137 publications
(59 citation statements)
references
References 19 publications
6
50
2
1
Order By: Relevance
“…Our previously reported association of DR1-DQ5 with CD [12,15,19,26] occurred as a trend in the present study (OR = 1.5, p = 0.068). However, the DR1 association was found attributable to the subtype DRB1*0103 in the combined Caucasian group of IBD patients, and this subtype was also significantly associated with both CD and UC patients (IBD: OR = 4.6, p = 0.001; CD: OR = 4.4, p = 0.002; and UC: OR = 4.9, p = 0.001).…”
Section: Dr1supporting
confidence: 74%
See 2 more Smart Citations
“…Our previously reported association of DR1-DQ5 with CD [12,15,19,26] occurred as a trend in the present study (OR = 1.5, p = 0.068). However, the DR1 association was found attributable to the subtype DRB1*0103 in the combined Caucasian group of IBD patients, and this subtype was also significantly associated with both CD and UC patients (IBD: OR = 4.6, p = 0.001; CD: OR = 4.4, p = 0.002; and UC: OR = 4.9, p = 0.001).…”
Section: Dr1supporting
confidence: 74%
“…For example, from earlier investigations using serologic methods, the frequency of the HLA class II serotype was increased in UC patients versus controls in most but not all European and United States Caucasian populations [7,13,15,[19][20][21][22]. In an English population study using DNA typing methods Satsangi et al found no association with DR2 in CD or UC patients [14].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…NOD2, the first gene linked with increased susceptibility to CD, has later been shown to be associated with ileal disease, early age of onset, stricturing, and/or penetrating phenotype and increased need for surgery [5,9,10,[38][39][40][41][42][43][44][45][46][47][48][49]. Among the UC susceptibility genes, HLA DRB1*0103 and the multidrug resistance gene 1 (MDR1/ABCB1) were also identified as being associated with extensive and severe disease [17,[23][24][25][26][27][28][29][30][31][32][33][34][35][36][37].…”
Section: Discussionmentioning
confidence: 99%
“…Among the UC susceptibility genes, HLA DRB1*0103 and the multidrug resistance gene 1 (MDR1/ABCB1) also contribute to clinical phenotype and natural history, being associated with extensive and severe disease [17,[23][24][25][26][27][28][29][30][31][32][33][34][35][36][37]. In CD, NOD2 gene mutations have repeatedly been shown to be associated with ileal disease, early age of onset, stricturing, and/or penetrating phenotype and increased need for surgery [5,9,10,[38][39][40][41][42][43][44][45][46][47][48][49].…”
Section: Introductionmentioning
confidence: 99%